Revitalizing Character-Based Total Quality Management: A Humanistic Solution to Addressing the Trend of Violence in Educational Institutions - Fuad, Harisun; Aimah, Siti (Ahlussunnah: Journal of Islamic Education, 2026)
This study aims to analyze the effectiveness of character-based Total Quality Management (TQM) revitalization as a humanistic solution to reduce the trend of violence in educational institutions. Given the increasingly alarming escalation of bullying and student aggression, this study employs a qualitative approach using a descriptive-analytical case study design at vocational high schools in Indonesia. Data were collected through participant observation, in-depth interviews with the principal, teachers, and students, and documentation of quality management protocols. Data analysis was conducted through the stages of data reduction, data presentation, and verification using content analysis and interpretive analysis techniques. The results of the study reveal three main findings: first, a paradigm shift from technical quality to humanistic quality, which prioritizes students’ psychological well-being as the highest quality indicator. Second, the implementation of Spiritual-based Service Excellence, grounded in the values of humility and tolerance, effectively transforms the role of educators into character mentors who help reduce students’ self-centeredness. Third, the application of Collaborative Governance through the “Character Quality Assurance Group” has successfully created an organic oversight system involving alumni, parents, and peers. The contribution of this research lies in the development of a Humanistic Total Quality Management model that offers empirical validation for educational institutions to transform administrative management systems into moral defense systems responsive to humanitarian crises and student safety.